Sustainability disclosure and mining company values - Chuzairi, Ahmad; Sutopo, Bambang (Islamic Accounting Journal, 2024)
Abstract Objective & object: This study aims to examine the influence of sustainability disclosure on firm value in mining companies listed on the Indonesia Stock Exchange during the 2021-2023 period. Methods: The research employs a quantitative explanatory approach with purposive sampling. The sample consists of mining companies listed on the Indonesia Stock Exchange that publish annual and sustainability reports. The number of samples used was 101 samples. Data analysis utilizes multiple regression with variables including the Sustainability Disclosure Index (SDI), firm size (SIZE), firm age (AGE), and profitability (ROA). Results & Conclusions: Findings reveal that sustainability disclosure positively and significantly affects firm value, alongside firm size and profitability. However, the level of sustainability disclosure remains relatively low, indicating room for improvement in transparency and regulatory compliance. Limitations: The study focuses solely on the mining sector and uses specific data from 2021-2023, which may limit the generalizability of the results. Implications: The results emphasize the need for enhanced regulatory frameworks to encourage comprehensive sustainability disclosure. Future research should explore other sectors and examine long-term implications. Keywords: Sustainability Disclosure, Firm Value, Size, Age, ROA Abstrak Tujuan & obyek: Penelitian ini bertujuan untuk menguji pengaruh pengungkapan keberlanjutan terhadap nilai perusahaan pada perusahaan tambang yang terdaftar di Bursa Efek Indonesia selama periode 2021-2023. Metode: Penelitian ini menggunakan pendekatan kuantitatif dengan metode explanatory. Sampel dipilih secara purposive dan terdiri dari perusahaan tambang yang menerbitkan laporan tahunan dan keberlanjutan. Jumlah sampel yang digunakan yaitu 101 sampel. Analisis data dilakukan dengan regresi berganda menggunakan variabel Sustainability Disclosure Index (SDI), ukuran perusahaan (SIZE), umur perusahaan (AGE), dan profitabilitas (ROA). Hasil & Simpulan: Hasil penelitian menunjukkan bahwa pengungkapan keberlanjutan berpengaruh positif dan signifikan terhadap nilai perusahaan, disertai pengaruh signifikan dari ukuran perusahaan dan profitabilitas. Namun tingkat pengungkapan keberlanjutan masih relatif rendah, sehingga perlu peningkatan transparansi dan kepatuhan regulasi. Keterbatasan: Penelitian ini hanya berfokus pada sektor pertambangan dan menggunakan data spesifik dari periode 2021-2023, yang dapat membatasi generalisasi hasil. Implikasi: Hasil penelitian menekankan pentingnya kerangka regulasi yang lebih kuat untuk mendorong pengungkapan keberlanjutan yang komprehensif. Penelitian lanjutan dapat memperluas cakupan sektor dan mengkaji implikasi jangka panjang. Kata kunci: Nilai Perusahaan, Pengungkapan Keberlanjutan, Size, Age, ROA